Prevention vs. treatment : what's the right balance? - Faust, Halley S.; Menzel, Paul T., 1942- (New York ; Oxford : Oxford University Press, 2011)
Is prevention better than cure, or treatment more important because people need rescue? In this volume the prevention-treatment relationship is examined factually by economists and scholars of health policy and evidence-based medicine.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Medicine, Preventive -- United States; Preventive health services -- United States; Evidence-based medicine -- United States